One-step lignocellulose fractionation using acid/pentanol pretreatment for enhanced fermentable sugar and reactive lignin production with efficient pentanol retrievability. (September 2022) - Madadi, Meysam; Zahoor,; Song, Guojie; Karimi, Keikhosro; Zhu, Daochen; Elsayed, Mahdy; Sun, Fubao; Abomohra, Abdelfatah
Graphical abstract: Highlights: Dilute acid (DA)/pentanol pretreatment was evaluated for whole biomass fractionation. More than 85% of non-cellulosic content were separated with 91% cellulose retention. DA/pentanol lignin showed medium molecular weights with high purity (98%). Pentanol protected abundant amount of β-O-4 from breakage and condensation. Pentanol is a promising solvent in pretreatment step of biomass conversion. Abstract: To valorize whole lignocellulosic biomass, this study proposed a biphasic solvent system using dilute acid (DA)/pentanol pretreatment. Effects of the key factors, i.e., temperature and pentanol concentration, on aspen were evaluated. Under identified optimal pretreatment conditions (160 °C, 60% pentanol), 85% and 91% of lignin and hemicellulose were solubilized in separate organic and liquid phases, respectively, while 91.1% of cellulose was retained in solid fraction. Enzymatic digestibility efficiency of pretreated cellulose was ∼ 6.4-times higher than that of untreated biomass. Notably, excellent pentanol recovery rates were obtained after four-times recycling (84%) with great cellulose digestibility (81%) and delignification (71%) performance. The recovered lignin contained low levels of contaminated sugars (<1%), while it could stabilize and protect high amounts of β-O-4 bonds. Besides, high phenolic OH content was found in lignin, which could be utilized for lignin-based biomaterials. Therefore, DA/pentanol pretreatment is an innovative promising technology for lignocellulosic valorization towards biorefinery.